The Performance Comparison between CPW-fed and Microstrip Feedline Leather Antenna for UWB Applications - N. H. M., Radi; M. M., Ismail; Z., Zakaria (UTeM Press, 2023)
In the area of wearable technology an enhancement of basic microstrip antenna is evolution of wearable textile antenna. A major requirement for wearable textile antenna is its flexible designed materials which incorporates of fabric in the structure. In this paper, the comparison between microstrip line and Coplanar Waveguide (CPW)-fed antenna design is presented. When the Federal Communication Commission (FSS) has allowed the operation of unlicensed ultra-wideband (UWB) thus it attracted research interest in realizing UWB antennas for wireless applications. The proposed microstrip antenna is designed, simulated and analyzed in Computer Simulation Technology (CST) Microwave Studio.The performance of antenna is analyzed for return loss bandwidth, and VSWR. The wide bandwidth and good performance of return loss are successfully achieved by using proposed design which implemented the CPW technique as compared with the transmission microstrip line technique.